Editorial: Stories That Unite, Stories That Divide - Irmina Rostek; Kamil Jezierski (Horyzonty Wychowania)
Over the past few years, the word “narrative” has appeared several times on the covers of “Horizons of Education”. Each time, we closed the issue with a sense of dissatisfac- tion and the conviction that the considerations that we had undertaken, certainly, had not run out the topics that interested us. Therefore, handing in this issue to you, we return with great joy once again to the reflection on narrative.